Correction: Towards high-throughput microfluidic Raman-activated cell sorting. Issue 19 (7th October 2015) - Zhang, Qiang; Zhang, Peiran; Gou, Honglei; Mou, Chunbo; Huang, Wei E.; Yang, Menglong; Xu, Jian; Ma, Bo
<x xml:space="preserve">Abstract</x> Correction for 'Towards high-throughput microfluidic Raman-activated cell sorting' by Qiang Zhang et al., Analyst, 2015, DOI: 10.1039/c5an01074h.